The Phantom Satiation Hypothesis of Bariatric Surgery - Gautron, Laurent (Frontiers in Neuroscience, 2021)
The excitation of vagal mechanoreceptors located in the stomach wall directly contributes to satiation. Thus, a loss of gastric innervation would normally be expected to result in abrogated satiation, hyperphagia, and unwanted weight gain. While Roux-en-Y-gastric bypass (RYGB) inevitably results in gastric denervation, paradoxically, bypassed subjects continue to experience satiation. Inspired by the literature in neurology on phantom limbs, I propose a new hypothesis in which damage to the stomach innervation during RYGB, including its vagal supply, leads to large-scale maladaptive changes in viscerosensory nerves and connected brain circuits. As a result, satiation may continue to arise, sometimes at exaggerated levels, even in subjects with a denervated or truncated stomach. The same maladaptive changes may also contribute to dysautonomia, unexplained pain, and new emotional responses to eating. I further revisit the metabolic benefits of bariatric surgery, with an emphasis on RYGB, in the light of this phantom satiation hypothesis.